2011
DOI: 10.1159/000335847
|View full text |Cite
|
Sign up to set email alerts
|

Cell Volume Regulation in Chondrocytes

Abstract: Chondrocytes are the cells within cartilage which produce and maintain the extracellular matrix. Volume regulation in these cells is vital to their function and occurs in several different physiological and pathological contexts. Firstly, chondrocytes exist within an environment of changing osmolarity and compressive loads. Secondly, in osteoarthritic joint failure, cartilage water content changes and there is a notable increase in chondrocyte apoptosis. Thirdly, endochondral ossification requires chondrocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 135 publications
2
70
0
Order By: Relevance
“…Finally, a sodium channel known to be functional in chondrocytes was studied (SCNN1A). 26 When quantitative PCR was performed on each of these genes to validate the microarray data, it was found that each ion channel mRNA was upregulated in OA sfMPCs compared to normal sfMPCs with the exception of KCNMA1, which had no change (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a sodium channel known to be functional in chondrocytes was studied (SCNN1A). 26 When quantitative PCR was performed on each of these genes to validate the microarray data, it was found that each ion channel mRNA was upregulated in OA sfMPCs compared to normal sfMPCs with the exception of KCNMA1, which had no change (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, reasonable to suggest that the overall capacity of these channels is dictated, at least in part, by their level of expression. Furthermore, the level of expression of these channels has been shown to differ in pathological cartilage, although whether this is causative or a result of the disease is unclear (24). In either case, altered expression could lead to progression of the disease and increased degeneration of the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, cells restore their original volume by activation of regulatory volume increase (RVI) mechanisms. Both RVD and RVI have mostly been investigated in mammalian cells [10], but also in cells of lower vertebrates and invertebrates [11,12,13]. With regard to invertebrates, we have previously demonstrated cell volume regulation in response to both hyposmotic and hypertonic stress in isolated nematocytes, and suggested the involvement of transport systems for multiple ions (namely Cl - and K + for RVD and Na + for RVI) and aquaporins in this regulation [9,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%